B. R. Ambedkar: Man and His Vision - Prakash, Arvind (Delhi Peridot Literary Books, 2019)
Bhimrao Ramji Ambedkar, popularly known as Babasaheb Ambedkar, was an Indian jurist, economist, politician and social reformer who inspired the Dalit Buddhist movement and campaigned against social discrimination towards the untouchables (Dalits), while also supporting the rights of women and labour.
Keywords: Labour Movement